Miscellaneous notes on specimens collected in Surat, Johanna Island and Cácota de Suratá, with emphasis on the Linnaean Herbarium (LINN) - de Moraes, Pedro Luís Rodrigues [UNESP] (Magnolia Press, 2023)
The aim of this paper was to investigate whether specimens in the Linnaean Herbarium (LINN), with Linnaean annotations of provenance as from Suratte/Suratt or Johanna Island, would be original material for their respective species names. As Linnaeus did not explicitly cite a specimen in the protolog of those names, neither the collector for most of them, the possible origin of each individual specimen was checked and searched from independent evidence, such as an explicit annotation, or a link to a dated list or letter among Linnaeus's surviving correspondence, or from Linnaeus's Paper Slips. Regarding the typification of those names, published choices of type have been found, but on a careful evaluation some were found to be ineffective or supersedable. This was the case for Cenchrus muricatus L. and Utricularia stellaris L.f., whose lectotypifications are proposed here.
Keywords: historical collections; nomenclature; taxonomy